2007
DOI: 10.1111/j.1467-6494.2007.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Contextualized Personality: Traditional and New Assessment Procedures

Abstract: We describe our ongoing program of research related to the assessment of contextualized personality, focusing on social roles and cultural cues as contextual factors. First, we present our research employing the traditional assessment approach, wherein participants are asked to rate explicitly their personality across several different roles. We argue that this hypothetical approach is potentially susceptible to the influence of stereotypes, social desirability, and demand characteristics. We therefore describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 42 publications
2
76
0
Order By: Relevance
“…Current models of personality suggest that personality is both a stable underlying trait and a dynamic process that emerges situationally. Previous attempts to assess personality using these models have focused on features of the physical environment (e.g., Ten Berge & De Raad, ) or on broad interpersonal roles (e.g., Heller et al., ; Wood, ). The current findings suggest that interpersonal relationships at a dyadic level can also be useful in conceptualizing personality.…”
Section: Discussionmentioning
confidence: 99%
“…Current models of personality suggest that personality is both a stable underlying trait and a dynamic process that emerges situationally. Previous attempts to assess personality using these models have focused on features of the physical environment (e.g., Ten Berge & De Raad, ) or on broad interpersonal roles (e.g., Heller et al., ; Wood, ). The current findings suggest that interpersonal relationships at a dyadic level can also be useful in conceptualizing personality.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research shows that when roles are situationally salient people exhibit traits (Heller, Watson, Komar, Min, & Perunovic, 2007) and pursue goals (Fitzsimons & Bargh, 2003) consistent with those roles. A recent study found that parents' moral judgments became more paternalistic when their parental role was salient than when it was non-salient (Eibach, Libby, & Ehrlinger, 2009).…”
mentioning
confidence: 92%
“…Any alternative to the established norm automatically enters unknown territories and is therefore "risky and dangerous", which is one of the main ideas that difficult change in the traditional evaluation. (Boud, Cohen, & Sampson, 1999;Heller, Watson, Komar, Min, & Perunovic, 2007;Maslovaty & Kuzi, 2002;Stoiber & Vanderwood, 2008).…”
Section: Regulation and Status Quo: Major Barriers For Oaolmentioning
confidence: 99%